Fluorescence properties of Baltic Sea phytoplankton - Seppälä, Jukka (Finnish Environment Institute, 2013)
To obtain data on phytoplankton dynamics (abundance, taxonomy, productivity, and physiology) with improved spatial and temporal resolution, and at reduced cost, traditional phytoplankton monitoring methods have been supplemented with optical approaches. Fluorescence detection of living phytoplankton is very sensitive and not disturbed much by the other optically active components. Fluorescence results are easy to generate, but interpretation of measurements is not straightforward as phytoplankton fluorescence is determined by light absorption, light reabsorption, and quantum yield of fluorescence - all of which are affected by the physiological state of the cells. In this thesis, I have explored various fluorescence-based techniques for detection of phytoplankton abundance, taxonomy and physiology in the Baltic Sea.In algal cultures used in this thesis, the availability of nitrogen and light conditions caused changes in pigmentation, and consequently in light absorption and fluorescence properties of cells. The variation of absorption and fluorescence properties of natural phytoplankton populations in the Baltic Sea was more complex. Physical environmental factors (e.g. mixing depth, irradiance and temperature) and related seasonal succession in the phytoplankton community explained a large part of the seasonal variability in the magnitude and shape of Chlorophyll a (Chla)-specific absorption. Subsequent variations in the variables affecting fluorescence were large; 2.4-fold for light reabsorption at the red Chla peak and 7-fold for the spectrally averaged Chla-specific absorption coefficient for Photosystem II. In the studies included in this thesis, Chla-specific fluorescence varied 2-10 fold. This variability in Chla-specific fluorescence was related to the abundance of cyanobacteria, the size structure of the phytoplankton community, and absorption characteristics of phytoplankton.Cyanobacteria show very low Chla-specific fluorescence. In the presence of eukaryotic species, Chla fluorescence describes poorly ...